Anticancer Activity Of Ethanol And Polyphenol Extracts Of Portulaca Quadrifida Linn. On Human Colon Cancer Cell Lines - SYED KAMIL MULLA,; PARAMJYOTHI SWAMY, (International Journal of Pharma and Bio Sciences, 2012)
Portulaca quadrifida Linn. (Portulacaceae) is traditionally used for the treatment against various ailments in tropical and subtropical parts of India without any scientific knowledge. Polyphenols, present in different fruits and vegetables, have retained attention in recent years. In the present study the effects of ethanol and polyphenol extracts of Portulaca quadrifida Linn. on the proliferation of Human colon cancer HT-29 and a normal L-6 cell lines were investigated by MTT assay and Trypan blue dye exclusion assay followed by DNA fragmentation assay. Total polyphenol content of both the extracts was determined by FCR method. Both ethanol and Polyphenol extracts efficiently decreased the proliferation of HT-29 cell lines. In addition the polyphenol extract exhibited fragmentation of DNA in HT-29 cell lines efficiently. Our results confirm that both extracts exhibited significant effect against HT-29 cell lines and are found less effective against normal L-6 cell lines indicating the cancer specific effect of Portulaca quadrifida Linn.